Rechtsfragen beim Wechsel des Rechtsregimes - Viertes Symposium der Juristischen Fakultät der Georg-August-Universität Göttingen mit der Yonsei Law School (Seoul) - Duttge, Gunnar; Kim, Jong Hwan (Universitätsverlag Göttingen, 2015)
The German reunification in 1989/90 is paradigmatic for fundamental geopolitical changes, in the context of a change of the entire legal system. Further well-known examples of the State's national desire for reformations with respect to legal principles are the great reform of the penal system in 1975, the reform of the law of obligations in 2002 and the fundamental reorganization of the law with respect to illiquid debtors. The Koreans are not only interested in the Germans' experience of the last quarter of a century because of legal-historical reasons, but also in particular because of the possible case of a Korean reunification. The present volume contains the contributions to the 4th symposium of the Faculty of Law of the Georg-August-Universität Göttingen and the Yonsei Law School (Seoul), which was held in Göttingen in February 2015.